KAJIAN SIFAT STRUKTUR KRISTAL PADA BAHAN BARIUM HEKSAFERIT YANG DITAMBAH VARIASI Fe2O3 MENGGUNAKAN ANALISIS RIETVELD - Kilat Permana Putra; Priyono Priyono (Jurusan Fisika, Fakultas Sains dan Matematika, Universitas Diponegoro, 2015)
Barium M - heksaferit known as permanent magnet material which has high competition against other classes of permanent magnet due to the manufacturing process is relatively simple, and has a high stability against heat and the external magnetic field besides having a high economic value. Problems encountered in the synthesis using stoichiometric composition was obtained despite the presence of a second phase in the composition of the minor.In this study the magnetic material synthesized using a non - stoichiometric composition by adding the compound Fe2O3 and conducted in-depth analysis on the initial temperature of formation at 950 0C, while the standard sample stoichiometric performed at a temperature of 1200 0C are entirely processed by powder metallurgy method using basic compound BaCO3 and Fe2O3 . Characterized using XRD to determine the crystal structure formed by the anode source Co which has a wavelength of 1.7889 Å on step scan 0,020. The results of XRD characterization followed by matching with international data ICDD - JCPDS then applied rietveld analysis using GSAS software. XRD characterization results showed the sample with stoichiometric composition of the Barium M-Hexaferrite (BaFe12O19) as main phase and a little Fe2O3 as a minor phase. With increasing 10% Fe the initial formation is dominated by BaFe2O4 intermediate phase at 950 0C. While the addition of 20% Fe is dominated by Fe2O3 phase.Rietveld analysis results for the material stoichiometric phase obtained better match value than both of samples while the best linearity was obtained at 20% Fe addition. Keywords: Powder Metalurgi, Barium Hexaferrite, XRD, Rietveld.